The Effect of Incubating Eggs under Different Lighting Conditions on Some Productivity and Blood Indicators of Broiler Chickens (Journal of Hama University, 2022)
This study was conducted to evaluate the effects of providing light during incubation on some productivity and immunological indicators in broiler chickens post hatching. 180 old day chickens were picked and divided into 3 described treatments groups (0, 12, and 24 h of photo-stimulation to eggs during incubation) having 3 replicates of 20 birds each, and the experiment was carried out for 42 days.There were no differences observed between the treatments in hatch weight (p> 0.05). However, Chicks hatched under 12 h of lighting had heavier body weight gain and less feed conversion ratio (P ≤ 0.05) than those of the other treatments during the only first week post placement. Furthermore, birds hatched under 12 h light had lower (P ≤ 0.05) in stress susceptibilities such as H/L ratio than those hatched under dark. Generally, the results of this study indicate that providing light during incubation has no positive effect on production of broilers, but does have potential benefits in terms of reducing the effects of stressors associated with production and growth. As well as, appropriate light stimuli (12 h) during incubation may help to improve hatching traits and post-hatch performance of commercial broiler.
Keywords: broiler, incubation, light, performance, blood indicators